Factors associated with delay to video-EEG in dissociative seizures. (March 2021) - Kerr, Wesley T.; Zhang, Xingruo; Hill, Chloe E.; Janio, Emily A.; Chau, Andrea M.; Braesch, Chelsea T.; Le, Justine M.; Hori, Jessica M.; Patel, Akash B.; Allas, Corinne H.; Karimi, Amir H.; Dubey, Ishita; et al.
Highlights: The mean delay to VEM was 8.4 years (median 3 years). Delay was associated with polytherapy and more ASM trials prior to VEM. Increased medical complexity was associated with longer delay. Access to healthcare through employment or school shortened delay. High seizure frequency was associated with shorter delay. Abstract: Purpose: While certain clinical factors suggest a diagnosis of dissociative seizures (DS), otherwise known as functional or psychogenic nonepileptic seizures (PNES), ictal video-electroencephalography monitoring (VEM) is the gold standard for diagnosis. Diagnostic delays were associated with worse quality of life and more seizures, even after treatment. To understand why diagnoses were delayed, we evaluated which factors were associated with delay to VEM. Methods: Using data from 341 consecutive patients with VEM-documented dissociative seizures, we used multivariate log-normal regression with recursive feature elimination (RFE) and multiple imputation of some missing data to evaluate which of 76 clinical factors were associated with time from first dissociative seizure to VEM. Results: The mean delay to VEM was 8.4 years (median 3 years, IQR 1–10 years). In the RFE multivariate model, the factors associated with longer delay to VEM included more past antiseizure medications (0.19 log-years/medication, standard error (SE) 0.05), more medications for other medical conditions (0.06 log-years/medication, SE 0.03), history of physical abuse (0.75 log-years, SE 0.27), and more seizure types (0.36 log-years/type, SE 0.11). Factors associated with shorter delay included active employment or student status (-1.05 log-years, SE 0.21) and higher seizure frequency (0.14 log-years/log[seizure/month], SE 0.06). Conclusions: Patients with greater medical and seizure complexity had longer delays. Delays in multiple domains of healthcare can be common for victims of physical abuse. Unemployed and non-student patients may have had more barriers to access VEM. These results support earlier referral of complex cases to a comprehensive epilepsy center.